THE IMPACT OF INCLUSIVE EDUCATION IN ISLAMIC BOARDING SCHOOLS ON THE CHARACTER DEVELOPMENT OF STUDENTS - Yaqin, Ainul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to examine the influence of inclusive education in Islamic boarding schools on the character formation of students. Inclusive education is expected to provide opportunities for all students, including those with special needs, to develop in a supportive atmosphere. The method used in this research is qualitative with a library research approach, where data is collected from various sources such as books, articles, journals and relevant official documents. The main findings show that inclusive education in Islamic boarding schools makes a positive contribution to the character development of students, especially in terms of tolerance, empathy and cooperation. Apart from that, this research also identifies the challenges faced in implementing inclusive education, including structural and cultural barriers. The significance of this research lies in its contribution to the development of inclusive education models in Islamic boarding schools and its implications for education policy in Indonesia.